PERAN LINGKUNGAN BELAJAR TERHADAP HASIL PEMBELAJARAN DAN KARAKTER PESERTA DIDIK - Amy Yuniati, Kusumaningrum; Diyan, Kusumawati; Putri Yudhiarti, Ndaru (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
Education is one of the most important elements in preparing a superior and advanced golden generation. Teachers as pillars in the implementation of education synergize with each other to form better quality students. The environment is an important basis for students in a meaningful learning process. The literature review conducted aims to determine the effect of the learning environment on learning outcomes and the formation of student character. The method used is Narrative Literature Review based on ten reference sources indexed by Google Scholar and Researchgate within the last three years period.. Based on the results of the literature study, it is found that a good learning environment can make learning more active, conducive and effective. A meaningful learning process makes students able to apply what they have learned well so that it can have an impact on the character that is formed for the students themselves. The learning environment is something that affects the learning result and the character building of students